The lectotype of Goliathus drurii Westwood, 1837 (Coleoptera: Scarabaeidae: Cetoniinae) in the Macleay Museum, University of Sydney, Australia - Blackburn, Robert (Zootaxa, 2016)
The lectotype of Goliathus drurii Westwood (Coleoptera: Scarabaeidae: Cetoniinae) has been located to the Macleay Museum, University of Sydney, Australia. Collected in 1775, this specimen represents the second species of Goliathus to be illustrated in European literature, however eluding a proper species description until 1837. This important specimen, overlooked by previous curators, represents another portion of the Dru Drury collections purchased by Alexander McLeay now held in the Macleay Museum.